TUTURAN ADAT FE HADAK BELIS MASYARAKAT TERMANU DESA PUKDALE KECAMATAN KUPANG TIMUR KABUPATEN KUPANG NUSA TENGGARA TIMUR : SEBUAH KAJIAN DALAM PERSPEKTIF LINGUISTIK KEBUDAYAAN - DEBI A INGUNAU (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2020)
This study examines forms, funcions, and meanings of Fe Hadak Belis speech: A Cultural Linguistics Analysis that specifically investigates characteristics of form, funcion, and meaning of Fe Hadak Belis speech. The objective of this study is to describe, to interpret, and to explain characteristics of the form, funcion, and meaning of Fe Hadak Belis speech in Rote community. The researcher conducted this study on February 3rd to 16th 2017. The method used to gain the data is descriptive qualitative with instruments interview, observation, recorder, and field notes. Data resources are Rote Termanu society specially Pukdale, Felakdale, and Tatebudale. In supporting the data, the researcher used main informant and comparison informant with the requirement that they should know the details of Fe Hadak Belis speech. The result of this result shows that the form of this speech is in form of lines in distich. Religion function of this speech is to show the honorary to God. The education of this speech is to give a lesson and a moral tothe society. While, social control function of this speech is to maintain rules of life of the society. The meaning which consisted in the Fe Hadak Belis speech are religious meaning as a faith acknowledgement of God, sociologic maning as a social control to maintain the relationship among the society, and esthetic meaning brings a beauty by the equality of consonant sound and equality of vocal sound.